Psychosocial interventions for supporting women to stop smoking in pregnancy - Chamberlain, Catherine; O'Mara-Eves, Alison; Porter, Jessie; Coleman, Tim; Perlen, Susan M.; Thomas, James; McKenzie, Joanne E. (Wiley, 2017)
Background: Tobacco smoking remains one of the few preventable factors associated with complications in pregnancy, and has serious long-term implications for women and babies. Smoking in pregnancy is decreasing in high-income countries, but is strongly associated with poverty and is increasing in low- to middle-income countries.